النقل متعدد الوسائط ومتطلبات تطبيقه في مرفأ اللاذقية - هرمز نور الدين; عبد الحي عماد الدين; احمد سامر (Latakia University Journal - Economic and Legal Sciences Series, 2014)
يعتبر النقل المتعدد الوسائط نظام قانوني جديد للنقل يهدف إلى تطوير وتفعيل النقل الدولي للبضائع، وأصبح جزء أساسي من السلسة اللوجستية العالمية التي تقوم في جوهرها على إيصال السلعة من المنتج إلى المستهلك بسرعة وأمان من خلال مجموعة من العمليات والخدمات اللوجستية ذات الكفاءة العالية في مختلف دول العالم. يتناول هذا البحث موضوع النقل المتعدد الوسائط وإمكانية تطبيقه في مرفأ اللاذقية باعتباره مرفأ الحاويات الأول في سورية. حيث سيتم وصف واقع مرفأ اللاذقية، ودراسة وتحليل مقومات النقل المتعدد الوسائط الأساسية كشبكة الطرق والسكك الحديدية التي تربط المرفأ بالمناطق الداخلية والمناطق الحرة والمرافئ الجافة ومنها إلى الدول المجاورة، إضافة إلى البنية التحتية والتكنولوجية في محطة حاويات مرفأ اللاذقية، وسيتم تسليط الضوء على عمل إدارة الجمارك باعتبار أن إصلاح العمل الجمركي وأتمتته من العوامل الأساسية لقيام نقل متعدد الوسائط فعّال. وبناءً على النتائج سيقدّم البحث بعض التوصيات لتفعيل النقل المتعدد الوسائط، وجعل مرفأ اللاذقية حلقة أساسية ضمن السلسلة اللوجستية للنقل الإقليمي والدولي. Multi-modal transport is a new legal transport system that aims to develop and activate the international transport of goods. It has become an essential part of the global supply chain, which is essentially based on safety and quick delivery of the product from producer to consumer, through a combination of highly efficient operations and logistics services in various countries of the world. This paper deals with the subject of multi-modal transport and the possibility applied in Lattakia port as it is the first container port in Syria. It also tries to describe the reality of Lattakia port, study and analysis the multi-modal transport elements as a network of roads and railways connecting the port inland areas and free zones to the neighboring states. The research also addresses the technological infrastructure in the container terminal of Lattakia port and focuses on the work of the customs administration, as the reform of the customs work and automatization of the fundamental factors are important for the establishment of an effective multimodal transport. Based on the results, the research presents some recommendations to activate the multi-modal transport and make Lattakia port an essential link in the logistical chain of regional and international transport.